2018
DOI: 10.2478/sc-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Educational Function of Media in Foreign Language Teaching

Abstract: The use of mass communication in the field of foreign language teaching is not a new phenomenon, because traditional media have been in use in this area for a few decades. Nowadays, however, several tendencies confirming the scale of this phenomenon can be observed. Mass media, and new media in particular, are used both in the process of self-education and as an important tool used by foreign language teachers. Technological progress, the communication revolution, the spread of the Internet, and the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…The results showed that this teaching approach can well attract students' attention. Bajorek & Gawroński [9] applied new media to English teaching and held that mass media, especially new media, were an important tool not only in the self-education process of English teachers, but also for English teachers. They stressed that technological progress, communication revolution, popularization of Internet and development of new media and mobile technology offered modern and effective ways to teach language.…”
Section: State Of the Artmentioning
confidence: 99%
“…The results showed that this teaching approach can well attract students' attention. Bajorek & Gawroński [9] applied new media to English teaching and held that mass media, especially new media, were an important tool not only in the self-education process of English teachers, but also for English teachers. They stressed that technological progress, communication revolution, popularization of Internet and development of new media and mobile technology offered modern and effective ways to teach language.…”
Section: State Of the Artmentioning
confidence: 99%
“…With the deepening of research on psychological behavior phenomenon in using network, the research of network learning self-efficacy has drawn increasingly more attention, especially in interactive foreign language teaching under the network environment (Bajorek & Gawroński, 2018). As the above research shows, the gender, the grade and the major category of learners are related with network environment learning efficacy.…”
Section: Resultsmentioning
confidence: 98%
“…Необхідність поширення соціолінгвістичних знань під час вивчення іноземної мови зумовлює використання допоміжного матеріалу задля оптимізації процесу навчання, насамперед матеріалу засобів масової інформації, що відображає життєві події носіїв мови та сучасні світові реалії. Питання ефективності використання матеріалу засобів масової інформації у процесі навчання було розглянуто та аргументовано у роботах вчених, серед них А. М. Калінін [6], Л. Є. Нагорнюк [11], K. Bajorek, S. Gawroński [19], V. Tafani [25] та інші.…”
Section: вступunclassified